Corporate Governance dan Kecurangan Laporan Keuangan (Studi Empiris Pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2019 – 2022) - Hidayat, Amelia Putri Eka Nur; Diana, Nur; Afifudin, Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research aims to determine and analyze the impact of corporate governance on financial statement fraud in property and real estate companies listed on the Indonesia Stock Exchange. Corporate governance is measured through managerial ownership, institutional ownership, the board of commissioners, and the audit committee. The type of research method used is quantitative method with a multiple linear regression analysis approach and data processing using the SPSS. This study has met the requirements of normality. The sample in this study used are secondary data obtained from the annual report of sample companies for the period 2019 – 2022. The variables used in this study are the dependent variable of institutional ownership, managerial ownership, audit committee, and commissioners and the independent variables are financial statement fraud. The results of the study show that managerial ownership, institutional ownership, and the audit committee do not have an effect on financial statement fraud. Meanwhile, the board of commissioners has a positive but not significant effect on financial statement fraud. These findings indicate that a good board of commissioner’s structure can reduce financial statement fraud. This study aims to enhance corporate governance theory and provide valuable insights for practitioners to improve supervisory mechanisms, thereby preventing financial statement fraud.Keyword: Institutional ownership, managerial ownership, audit committee, and commissioners, financial statement fraud